Regulation of Spiral Ganglion Neuron Regeneration as a Therapeutic Strategy in Sensorineural Hearing Loss - Wang, Man; Xu, Lei; Han, Yuechen; Wang, Xue; Chen, Fang; Lu, Junze; Wang, Haibo; Liu, Wenwen (Frontiers in Molecular Neuroscience, 2022)
In the mammalian cochlea, spiral ganglion neurons (SGNs) are the primary neurons on the auditory conduction pathway that relay sound signals from the inner ear to the brainstem. However, because the SGNs lack the regeneration ability, degeneration and loss of SGNs cause irreversible sensorineural hearing loss (SNHL). Besides, the effectiveness of cochlear implant therapy, which is the major treatment of SNHL currently, relies on healthy and adequate numbers of intact SGNs. Therefore, it is of great clinical significance to explore how to regenerate the SGNs. In recent years, a number of researches have been performed to improve the SGNs regeneration strategy, and some of them have shown promising results, including the progresses of SGN regeneration from exogenous stem cells transplantation and endogenous glial cells reprogramming. Yet, there are challenges faced by the effectiveness of SGNs regeneration, the maturation and function of newly generated neurons as well as auditory function recovery. In this review, we described recent advances of researches in SGNs regeneration. In the coming years, regenerating SGNs in the cochleae should become one of the leading biological strategies to recover hearing loss.